PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWTOON PADA POKOK BAHASAN STRUKTUR ATOM DI KELAS X SMA/SEDERAJAT - ', Juliana; ', Erviyenni; ', Rini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is a Research and Development (R & D). The development process has been done with reference to ADDIE model with steps of Analyze, Design, Development, Implementation, Evaluation. Research was conducted in FKIP UR. This research aims to obtain the learning media chemistry using by powtoon on subject of the atomic structure. The research and development with ADDIE model was conducted only until Development step, because the purpose of this research was limited to develop and produce a feasiblity the learning media chemistry using by powtoon to be implemented based on validator assessment. Feasibility of the learning media chemistry using by powtoon was evaluated from feasibility of the design, pedagogy, content, ease of use,the view and programming Of the learning media chemistry validation result of validation by media experts and material obtained an average value as 86,31% which showed that learning media chemistry using by powtoon which developed was feasiblity. The result of the development has been test in two teachers and 20 students, average score percentase obtained by 82,14%.Key Words : Development of learning media, PowToon, and Atomis Structure